A Triangulated Study of Academic Language Needs of Iranian Students of Computer Engineering: Are the Courses on Track? - Atai, Mahmood Reza; Shoja, Leila (RELC Journal, 2011)
Even though English for Specific Academic Purposes (ESAP) courses constitute a significant part of the Iranian university curriculum, curriculum developers have generally developed the programs based on intuition. This study assessed the present and target situation academic language needs of undergraduate students of computer engineering. To this end, data were elicited from 231 undergraduates, 30 graduate students, 20 computer engineering instructors and 15 ESP instructors at three major Iranian universities. Instrumentation included needs analysis and self-assessment questionnaires, a general English proficiency test, semi-structured interviews, and non-participant observations. Despite some inconsistencies in participants’ perceptions of target situation needs, the findings indicate that written skills and language components are important. The undergraduates perceived difficulties with some sub-skills of reading, writing, speaking, and listening. Moreover, General English Proficiency (GEP) level of the students, as probed by a GEP test and confirmed by self assessment results and teacher assessment data, was generally low. The undergraduates held that they need more general English than highly specific academic English. Finally, participants commented on several major problematic areas. The findings may promise implications for renewing the ESAP course under study and suggest a model framework for needs assessment to other EASP researchers worldwide.